2011
DOI: 10.1890/es11-00096.1
|View full text |Cite
|
Sign up to set email alerts
|

Integral projection model of insect herbivore effects onCirsium altissimumpopulations along productivity gradients

Abstract: Abstract. Prediction of the role of native insect herbivores in the population growth and spatial distribution of native plants within the environment remains limited. We developed an integral projection model (IPM) to explore the effect of native insect herbivores on the population dynamics and distribution of the native plant Cirsium altissimum (tall thistle), in two different productivity zones in tallgrass prairie in Nebraska USA. Model parameters were extracted from two field experiments: a seed addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
(100 reference statements)
3
12
0
Order By: Relevance
“…These findings are consistent with experimental studies showing that insect herbivory often severely reduce the fecundity of thistles (Louda and Potvin 1995;Rose et al 2005Rose et al , 2011Suwa et al 2010). Similar to the native C. altissimum, the late flowering time of C. vulgare combined with the occurrence of late-season herbivores, such as Homoeosoma eremophasma (Pyralidae) (Takahashi 2006), likely prevent successful compensatory seed production (Rose et al 2011).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These findings are consistent with experimental studies showing that insect herbivory often severely reduce the fecundity of thistles (Louda and Potvin 1995;Rose et al 2005Rose et al , 2011Suwa et al 2010). Similar to the native C. altissimum, the late flowering time of C. vulgare combined with the occurrence of late-season herbivores, such as Homoeosoma eremophasma (Pyralidae) (Takahashi 2006), likely prevent successful compensatory seed production (Rose et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…However, the results here demonstrate that the magnitude of the effect was more severe for the nonnative C. vulgare. We found that the Δλ (λ herbivores absent − λ herbivores present) was 1.42 for C. vulgare (above), compared to 0.80 for C. altissimum (Rose et al 2011). Further, the effects of native insect herbivory on C. vulgare population growth quantified here were more severe than those observed on average in other native plant populations (average Δλ = 0.04) (Maron and Crone 2006;Miller et al 2009) and in populations of another related native thistle species, Cirsium canescens (Δλ = 0.33) (Rose et al 2005).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Numerous previous studies have demonstrated that, at low density, grasshopper herbivory usually has neutral (Gibson et al 1990;Whiles and Charlton 2006;Rose et al 2011) or limited effects on grassland plant growth (biomass loss <10 %) in North America and China (Hewitt et al 1976;Fry et al 1978;Hewitt and Onsager 1982;Landsberg and Ohmart 1989;Tilman 1992, 1993;Redak and Capinera 1994;Carson and Root 1999;Coupe and Cahill 2003;Kula et al 2005;Fielding 2005, 2008;Orians et al 2011;Zhang et al 2011;Suwa and Louda 2012). However, locusts at a similar density could cause more severe damage (30 % (Loranger et al 2014), or at high elevation (Blumer and Diemer 1996).…”
Section: Discussionmentioning
confidence: 99%